Prioritization of Factors Influencing Business Incubator – A Perspective Study - Dr. Suman Naredla, Mr. Vinay Kumar Pothula (International Journal of Advanced Science and Technology, 2020)
The nation is prospered when the citizens of the nation had good living conditions concerning their economics. It is the primary responsibility of any nation to design job avenues (earning sources) for their citizens. Highly populated countries like India need to figure out more strategies for creating such avenues and way to motivate citizens with an entrepreneurial mind-set to attempt. Creating an environment to establish more companies would yield better results such that, the nations have introduced Business Incubators (BIs). BIs that attract Investors across the globe and helps countries economically viable. The main intension behind establishing business incubators is to support start-ups that are facing a higher mortality rate of around 75 to 80% in the current economic world.